2019
DOI: 10.1016/j.actamat.2019.02.026
|View full text |Cite
|
Sign up to set email alerts
|

In-situ XRD study of actuation mechanisms in BiFeO3-K0.5Bi0.5TiO3-PbTiO3 ceramics

Abstract: In the present study, we report a nonergodic relaxor ferroelectric composition for high temperature piezoelectric applications, 0.57BiFeO 3-0.21K 0.5 Bi 0.5 TiO 3-0.22PbTiO 3 , which exhibits T m around 420 °C. By combining the results of in-situ synchrotron XRD and strain measurements using digital image correlation, a pseudocubic nonergodic relaxor to rhombohedral ferroelectric transformation is identified, accompanied by a volume strain close to zero. A methodology is developed to determine the crystallogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…In this work, three kinds of XRD measurements were designed. Rietveld refinement on XRD data was carried out on the KNNS–BKH powder measured at different temperatures (20–200 °C) to analyze the intrinsic structure information without any influence of external electric fields, during which Findit and MAUD software were employed. For better illustration of the in situ d 33 , the in situ XRD of the poled samples was measured from 20 to 250 °C. And the XRD patterns of the samples after they were poled at 20, 50, 70, and 100 °C were also measured.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, three kinds of XRD measurements were designed. Rietveld refinement on XRD data was carried out on the KNNS–BKH powder measured at different temperatures (20–200 °C) to analyze the intrinsic structure information without any influence of external electric fields, during which Findit and MAUD software were employed. For better illustration of the in situ d 33 , the in situ XRD of the poled samples was measured from 20 to 250 °C. And the XRD patterns of the samples after they were poled at 20, 50, 70, and 100 °C were also measured.…”
Section: Methodsmentioning
confidence: 99%
“…Macroscopic structural transformations in perovskites are characterised by changes in {111} p and {200} p peak profiles prior to and after application of the field. [19][20][21][22][23][24][25] Initially, in this contribution, the macroscopic strain is evaluated by observation of {111} p , {200} p and {220} p peaks at 60 kV cm -1 with a step of 5 kV cm -1 . [12,19] Measurements parallel (β = 0°) and perpendicular (β = 90°) to the direction of the field illustrate any domain re-orientation and associated lattice strain.…”
Section: Full-pattern Rietveld Refinement and Transmission Electron Microscopy (Zero Field)mentioning
confidence: 99%
“…[15,28] The domain switching behaviour in polycrystalline ferroelectric ceramics leads to anisotropic dimensional deformation, as well as lattice strain. According to Jones and co-workers [20,21,28], the spontaneous strain for single crystal distortion associated with non-180° domain switching for a rhombohedral cell can be defined as follows:…”
Section: Full-pattern Rietveld Refinement and Transmission Electron Microscopy (Zero Field)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Ta doping greatly accelerated the crystal growth, which leads to certain sets of split diffraction peaks in AgNb 1– x Ta x O 3 gradually converging into single peaks (Figure S1). All Bragg reflections shift toward higher angles, including 2θ at 22.6 and 52.1°, which generally leads to a shrinking lattice volume and a different electronic structure. , Therefore, it is significant to know about the mechanism of the doping effect in niobium and tantalum solid solutions.…”
Section: Resultsmentioning
confidence: 99%